Results of Modified Gil-Vernet Antireflux Surgery in the Treatment of Vesicoureteral Reflux - Irani, Darioush; Heidari, M (Urology Journal, 2009)
Purpose: To evaluate the efficacy of modified Gil-Vernet anti-reflux surgery in the treatment of patients with primary vesicoureteral reflux in a prospective historical controlled trial. Materials and Methods: A total of 30 patients with 46 refluxing units underwent this surgery since February 1998 until September 2002, with the mean follow-up period of 18 (range 6 to 43) months. Results: Vesicoureteral reflux was resolved completely in 44 ureteral units (95.6%, P < 0001). In 2 refluxing units (4.3%) in spite of reflux improvement, hydroureter remained unchanged after the surgery. In respect to response rate, there was no significant difference between different grades, genders, age groups, and laterality of primary vesicoureteral reflux. Conclusion: Our findings indicate that modified Gil-Vernet anti-reflux surgery which separately transfers each ureteral orifice to the tip of trigone with two fine absorbable suture on each side, is a completely successful procedure in the treatment of primary vesicoureteral reflux and produces a longer submucosal tunnel with a more suitable angel than classic Gil-Vernet procedure dose.